Hubungan Antara Persepsi Anggota Tentang Perencanaan Progam Dan Pengawasan Program Kerja Terhadap Efektifitas Kerja Anggota Pada Ditlantas Polda Metro Jaya Jakarta - Delvy Servia; Muhamad Arief Noor; Joned Ceilendra Saksana (Indo Publishing, 2025)
This study aims to analyze the relationship between members' perceptions of program planning and work program supervision and their work effectiveness at the Traffic Directorate of the Jakarta Metro Jaya Regional Police. The background of this research is based on the importance of work effectiveness in supporting the performance of public organizations, particularly the police, which plays a strategic role in public service. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to members of the Traffic Directorate of the Jakarta Metro Jaya Regional Police, using multiple linear regression analysis to test the relationships between variables. The results indicate a positive and significant relationship between members' perceptions of program planning and work effectiveness, as well as between work program supervision and work effectiveness. Simultaneously, members' perceptions of program planning and work program supervision significantly influence members' work effectiveness. These findings confirm that good planning and supervision can improve members' performance in carrying out their duties and responsibilities. This research provides a practical contribution to strengthening the managerial system within the police force and serves as a reference for data-driven policymaking.